2022
DOI: 10.1177/15347346221076625
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Topical Solution of Diperoxochloric Acid for Neuropathic Diabetic Foot Ulcer: Results from a Phase 3, Multicentre, Randomized, Active-controlled, Parallel-group Study

Abstract: Diabetic foot ulcer (DFU), if untreated, accounts for lower-limb amputations affecting patients’ quality-of-life. Diperoxochloric acid (DPOCL) is known to heal DFU by its antibacterial and fibroblast stimulating activity. This was a phase 3, multicentre, randomized, double-blind, active-controlled, parallel-group study conducted to evaluate the efficacy and safety of topic solution of DPOCL compared with isotonic sodium chloride solution (ISCL). Adult patients with type 1 or 2 diabetes with random blood glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…We found one study comprising 324 participants, which was assessed as being at moderate risk of bias, which evaluated the efficacy of diperoxochloric acid as a topical solution compared with isotonic sodium chloride solution in diabetic foot ulcers. 29 It reported a significantly greater proportion achieving complete wound healing at 10 weeks, but offloading was not standardised and the results of the a per protocol analysis were reported only. Participants were mainly hospitalised and thus the generalisability of this result is unclear.…”
Section: Agents With Antiseptic/antimicrobial Effectsmentioning
confidence: 99%
See 3 more Smart Citations
“…We found one study comprising 324 participants, which was assessed as being at moderate risk of bias, which evaluated the efficacy of diperoxochloric acid as a topical solution compared with isotonic sodium chloride solution in diabetic foot ulcers. 29 It reported a significantly greater proportion achieving complete wound healing at 10 weeks, but offloading was not standardised and the results of the a per protocol analysis were reported only. Participants were mainly hospitalised and thus the generalisability of this result is unclear.…”
Section: Agents With Antiseptic/antimicrobial Effectsmentioning
confidence: 99%
“…Four of the above studies also reported time to healing 23,26,27,29 with a further study 32 investigating time to healing using a gentamicin sponge.…”
Section: Outcome: Time To Healingmentioning
confidence: 99%
See 2 more Smart Citations
“…Given this is a large group of interventions, we have broken down the key recommendations into smaller sections based on the groups of types of products and applications currently available. Rationale: We found 12 studies [27][28][29][30][31][32][33][34][35][36][37][38] evaluating anti-septic or antimicrobial dressings or topical antiseptic applications. Five evaluated the use of silver impregnated dressings in comparison with usual care [27][28][29][30]37 but all were considered at high or moderate risk of bias.…”
Section: Intervention: Dressingsmentioning
confidence: 99%